(untitled) (Comprehensive Journal of Science, 2024)
Achieving environmental sustainability is one of the most prominent challenges facing the world. Achieving a healthy global ecosystem that supports the Earth and is sustainable for life has become a priority for countries around the world and international organizations that seek to achieve environmental sustainability for the safe consumption of natural resources and their protection to meet the needs of the current and future generations. Despite the efforts made to achieve environmental sustainability, the world faces many challenges that hinder its achievement. From this standpoint, this study came to define green technology and its importance in achieving environmental sustainability and the applications used, which in turn seek to reduce the negative impact of human activities on the environment, by innovating environmentally friendly technologies that help reduce greenhouse gas emissions, protect the environment and achieve its sustainability, and enhance the country’s economic growth in a sustainable manner.